Size-dependent melting modes and behaviors of Ag nanoparticles: a molecular dynamics study. (7th November 2017) - Liang, Tianshou; Zhou, Dejian; Wu, Zhaohua; Shi, Pengpeng
Abstract: The size-dependent melting behaviors and mechanisms of Ag nanoparticles (NPs) with diameters of 3.5–16 nm were investigated by molecular dynamics (MD). Two distinct melting modes, non-premelting and premelting with transition ranges of about 7–8 nm, for Ag NPs were demonstrated via the evolution of distribution and transition of atomic physical states during annealing. The small Ag NPs (3.5–7 nm) melt abruptly without a stable liquid shell before the melting point, which is characterized as non-premelting. A solid-solid crystal transformation is conducted through the migration of adatoms on the surface of Ag NPs with diameters of 3.5–6 nm before the initial melting, which is mainly responsible for slightly increasing the melting point of Ag NPs. On the other hand, surface premelting of Ag NPs with diameters of 8–16 nm propagates from the outer shell to the inner core with initial anisotropy and late isotropy as the temperature increases, and the close-packed facets {111} melt by a side-consumed way which is responsible for facets {111} melting in advance relative to the crystallographic plane {111}. Once a stable liquid shell is formed, its size-independent minimum thickness is obtained, and a three-layer structure of atomic physical states is set up. Lastly, the theory of point defect-pair (vacancy-interstitial) severing as the mechanism of formation and movement of the solid-liquid interface was also confirmed. Our study provides a basic understanding and theoretical guidance for the research, production and application of Ag NPs.